ENHANCING INTER-ORGANIZATIONAL COLLABORATION FOR HUMANITARIAN DEVELOPMENT: YEMEN AS A CASE STUDY - Areeg Gamil (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study investigates the improvement of inter-organizational collaboration for humanitarian development, with a particular emphasis on cash programming initiatives in Yemen. The study aims to boost the effectiveness and durability of these activities by addressing barriers to efficient collaboration between humanitarian organizations and government authorities. It assesses targeting tactics to guarantee that help reaches the neediest populations and examines how economic and political factors influence program execution. The study used a qualitative research design, relying on secondary data from publications, reports, surveys, and humanitarian databases to evaluate the effectiveness of cash transfer programs. Case studies of existing financial assistance programs in Yemen are also investigated to discover successful models and implementation issues. The findings show that, while cash-based assistance has greatly improved the living conditions of Yemen's most vulnerable inhabitants, structural difficulties such as fragmented coordination, political instability, and economic volatility limit its efficacy. The study emphasizes the necessity of inter-organizational collaboration, the implementation of unified social registration systems, and the use of intersectional targeting strategies to improve program inclusion and efficiency. Furthermore, the study emphasizes the importance of enhanced governance and accountability structures to ensure the long-term impact of cash-based programming programs. The study suggests that improving inter-organizational collaboration, developing new targeting strategies, and addressing governance deficiencies are critical to increasing the resilience and sustainability of humanitarian operations in Yemen. Future studies should focus on assessing the long-term effects of cash-based programs, as well as investigating the role of digital alternatives in increasing assistance distribution transparency and efficiency. This study adds to the greater discussion on humanitarian relief by giving actionable ideas for improving cash programming in conflict-affected areas.